Analytical Investigation of a Beam on Elastic Foundation with Nonsymmetrical Properties - Iwona Małgorzata WSTAWSKA; Krzysztof MAGNUCKI; Piotr KĘDZIA (Engineering Transactions, 2022)
The subject of presented analytical and numerical investigation is the stability of  an axially compressed beam on an elastic foundation. The shape function of the foundation was assumed. The formula was supplemented with the offset parameter. The critical values of loads were calculated and presented as a function of geometric and mechanical properties of the beam and nonsymmetrical properties of the elastic foundation. The highest values of critical loads can be obtained for the highest values of shape parameter and the lowest values of amplitudes of shape function. The values of critical loads increase with the increase of the value of the offset parameter.